Evaluating the interfacial toughness of GaN-on-diamond with an improved analysis using nanoindentation. (1st March 2022) - Field, Daniel E.; Beale, Ryan; Getzler, Naomi; Pomeroy, James W.; Leide, Alexander J.; Francis, Daniel; Twitchen, Daniel; Faili, Firooz; Liu, Dong; Kuball, Martin
Abstract: An improved analysis of the interfacial toughness using nanoindentation induced blistering of thin films on stiff substrates is demonstrated on GaN-on-diamond. The Hutchinson-Suo analysis requires accurate measurement of blister dimensions, conventionally measured using 2-D line-scans from 3-D topographical maps. The new meteorology overcomes shortcomings of this technique by fitting the 3-D analytical solution of a clamped Kicrchoff plate to the topological map of the blister. This allowed for quantification of interfacial toughness of smaller blisters in GaN-on-diamond, previously assumed invalid for analysis due to inadequacies of the line-scan analysis. Three samples were investigated and found to have interfacial toughness ranging from 0.6–1 J m −2 . Additionally, the relationship between residual stress in the GaN and interfacial toughness was investigated using photoluminescence spectroscopy. In all cases, the GaN was found to be under increased compression at the diamond interface by up to -0.81 GPa, although no correlation with interfacial toughness was observed. Graphical abstract: Image, graphical abstract